Psoriasis and cardiomyopathy: An intriguing association - Prakash Anupam; Deepshikha (Wolters Kluwer Medknow Publications, 2010)
A 25-year-old male symptomatic of heart disease for four months presented with biventricular failure. Echocardiography revealed dilated cardiomyopathy. He had skin lesions for 10 years which were clinically and histopathologically identified as psoriasis. Association of cardiomyopathy with psoriasis is uncommon and intriguing. The link between dilated cardiomyopathy and psoriasis on a common inflammatory background is discussed.